Adaptive Learning Techniques for a Personalized Educational Software in Developing Teachers’ Technological Pedagogical Content Knowledge - Christodoulou, Andri; Angeli, Charoula (Frontiers in Education, 2022)
The authors discuss the design and utilization of e-TPCK, a self-paced adaptive electronic learning environment designed to promote the development of teachers' Technological Pedagogical Content Knowledge (TPCK). The system employs a technological solution that promotes teachers' ongoing TPCK development by engaging them in personalized learning experiences using technology-infused design scenarios. Results from an experimental research study revealed that the experimental group outperformed the control group in developing TPCK on two design tasks, substantiating the claim that technology can better facilitate the development of TPCK than traditional instruction. Furthermore, e-TPCK's adaptive guidance using worked-out examples led to mathemagenic learning effects for novice student-teachers, while for the more experienced student-teachers learning with e-TPCK proved beneficial only at the beginning of their engagement with the system. Hence, the relative effectiveness of instructional techniques embedded in e-TPCK became less effective due to student-teachers' increasing expertise. In conclusion, the findings of the research are encouraging for the advantages of personalized learning in teacher education and showed that the design of adaptive learning technologies must account for learners' prior knowledge and changing levels of expertise throughout the ongoing interaction with the computer system.